Gospels and tradition studies on redaction criticism of the Synoptic Gospels - Stein, Robert H. 1935- (Grand Rapids, MI Baker, 1991)
Includes bibliographical references and index.
Keywords: Bible. N.T. Gospels -- criticism, redaction